2020
DOI: 10.37092/el-ghiroh.v18i2.243
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Supervisi Akademik Dalam Meningkatkan Kualitas Pembelajaran di SMA dan SMK Se-Kecamatan Abung Semuli Lampung Indonesia

Abstract: Motivated by the problems of the quality of learning. To improve the quality of teaching carried out by teachers, through educational supervision. The research was conducted in SMA and SMK in Abung Semuli Subdistrict, Lampung which aims to describe the Principal's knowledge regarding the role of supervisor and to know the Implementation of Academic Supervision in Improving the Quality of Teacher Learning. Research using a qualitative research approach with phenomenological theory. Conclusions: Principals of SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Findings in the field show that the principal of the Grobogan Regency Vocational School conducted a review of the class, asked teachers to take part in training/workshops, and held discussions with teachers regarding the problems faced in the teaching process. The conditions encountered were in accordance with the theory expressed by Ningsih et al, (2020). In fact, based on testing using path analysis, it is known that there is an impact of academic supervision on the quality of learning.…”
Section: The Impact Of Teaching Infrastructure On Improving the Quali...supporting
confidence: 78%
See 1 more Smart Citation
“…Findings in the field show that the principal of the Grobogan Regency Vocational School conducted a review of the class, asked teachers to take part in training/workshops, and held discussions with teachers regarding the problems faced in the teaching process. The conditions encountered were in accordance with the theory expressed by Ningsih et al, (2020). In fact, based on testing using path analysis, it is known that there is an impact of academic supervision on the quality of learning.…”
Section: The Impact Of Teaching Infrastructure On Improving the Quali...supporting
confidence: 78%
“…Several studies have revealed academic supervision by school principals. Research by Ningsih et al, (2020) revealed that school principals in carrying out academic supervision can provide guidance to teachers in preparing syllabi, learning plans, determining appropriate learning methods and media, and sending teachers to participate in skills development training in teaching. Findings in the field show that the principal of the Grobogan Regency Vocational School conducted a review of the class, asked teachers to take part in training/workshops, and held discussions with teachers regarding the problems faced in the teaching process.…”
Section: The Impact Of Teaching Infrastructure On Improving the Quali...mentioning
confidence: 99%
“…The implementation of class visits can be stated that class visits or classroom supervision are carried out at least once a year, with the principal as a supervisor or assisted by senior teachers whom the principal trusts to become supervisors because of the large number of teachers who must be supervised (Ningsih et al, 2020). Based on the results of interviews with G2 at MTsN 1 Makassar City itself, academic supervision on learning implementation is also carried out once a year.…”
Section: "Supervisi Dalam Pelaksanaan Pembelajaran Dilaksanakan Oleh ...mentioning
confidence: 99%